The text of the Pentateuch textual criticism and the Dead Sea Scrolls - Crawford, Sidnie White 1960- (De Gruyter, 2022)
In the last several decades since the first publications of the biblical Dead Sea Scrolls, a revolution has occurred in the understanding of the history of the text of the Hebrew Bible during the Second Temple period. The present volume is a collection of articles documenting that revolution, written by Sidnie White Crawford over an almost thirty-year period beginning in 1990. As a member of the editorial team responsible for publishing the Qumran scrolls, the author was responsible for the critical editions of nine Deuteronomy scrolls and the four Reworked Pentateuch manuscripts; thus, her work played a critical role in the changing understanding of the textual history of the Pentateuch,especially the book of Deuteronomy and the Rewritten Bible texts. The author's lifework is brought together here in an accessible format. While the majority of the articles are reprints, the volume will close with two major new pieces: a text-critical study of the Deuteronomic Paraphrase of the Temple Scroll and a comprehensive overview of the history of the text of the Pentateuch
Keywords: Bibel -- Pentateuch; Qumrantexte; Bibel -- Deuteronomium; Bibel; Deuteronomium; Qumran-Schriften; Textkritik; RELIGION / Biblical Criticism & Interpretation / Old Testament; Rezeption; Textgeschichte; Frühjudentum; Aufsatzsammlung